#### Answer

y=13

#### Work Step by Step

Simplifying
4y + 11 = 7y + -28
Reorder the terms:
11 + 4y = 7y + -28
Reorder the terms:
11 + 4y = -28 + 7y
Solving
11 + 4y = -28 + 7y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-7y' to each side of the equation.
11 + 4y + -7y = -28 + 7y + -7y
Combine like terms: 4y + -7y = -3y
11 + -3y = -28 + 7y + -7y
Combine like terms: 7y + -7y = 0
11 + -3y = -28 + 0
11 + -3y = -28
Add '-11' to each side of the equation.
11 + -11 + -3y = -28 + -11
Combine like terms: 11 + -11 = 0
0 + -3y = -28 + -11
-3y = -28 + -11
Combine like terms: -28 + -11 = -39
-3y = -39
Divide each side by '-3'.
y = 13
Simplifying
y = 13